World class : teaching and learning in global times - Gaudelli, William (L. Erlbaum Associates, 2003)
How have school curricula been affected by the ripple effects of globalization? How do teachers and students attempt to understand their complex world? Most states require world teaching in some form, yet little is known about how teachers and students engage in this critical curricular area. World Class: Teaching and Learning in Global Times directly fills this need by providing a detailed, inside look at global education in three high schools. The data from the study, drawn from extensive interviews and observations, illustrate the daily challenges a.